THE CONCEPT OF NATURE IN THE POLITICAL PHILOSOPHY OF THE AMERICAN TRANSCENDENTALISTS OF R. W. EMERSON AND H. D. THOREAU - Liebiedieva, Hanna (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2024)
B a c k g r o u n d . The article examines the interconnection between the philosophy of nature and the political philosophy of the transcendentalists R. W. Emerson and H. D. Thoreau. For these thinkers, political philosophy was intrinsically linked to their understanding of nature, which they considered the foundation for comprehending social and political processes. Both transcendentalists emphasized the importance of unity with nature as a key factor in personal development. They regarded individual growth as the cornerstone for positive societal changes, with particular attention given to individualism. Their support for the actions of J. Brown exemplified the practical realization of the ideas of political idealism and transcendentalism. In their view, the primary aim of government should be to promote individuality and improve the conditions of human existence, which led them to actively oppose the system of slavery. M e t h o d s . A comprehensive methodological approach was employed to analyze the political philosophy of R. W. Emerson and H. D. Thoreau in the context of their philosophy of nature. This included general scientific methods, historical-philosophical methods, and specific techniques, such as the hermeneutic approach. Additionally, the method of historical reconstruction was used to highlight the socio-political context of their ideas. R e s u l t s . The study revealed the deep integration of Emerson's and Thoreau's political philosophy into their concept of nature, as well as its connection to the socio-political conditions of their era. American transcendentalism occupies a unique place not only in the history of early American philosophy but also within the broader scope of English-speaking philosophy. It blended German idealism, Neoplatonism, and Eastern mysticism, forming a distinctive eclectic doctrine that offered a unique perspective on nature, human nature, rights and freedoms, education, physical labor, individualism, and collectivism. American transcendentalism directly and indirectly influenced the development of American pragmatism, as evidenced in the works of pragmatists such as J. Dewey, C. S. Peirce, and W. James. Its influence is also evident in the literary heritage of H. Melville, N. Hawthorne, W. Irving, and others. C o n c l u s i o n s . The political philosophy of R. W. Emerson and H. D. Thoreau was grounded in their understanding of natural laws, the importance of civic education and education in general, unity with nature, and respect for the individual. They regarded slavery as an unnatural social order, opposition to which they considered a moral duty for citizens aspiring to build a harmonious society.